The rise and fall of CCAC : a case study in heritage politics : a thesis presented in partial fulfilment of the requirements for the degree of Master of Arts in Museum Studies at Massey University - McCarthy, Kerry (Massey University, 1998)
Museums are publicly funded community organisations. In New Zealand today most museum funding is provided by local governments but central government also plays a role. Fundamental to museum activity is the preservation of collections which are assembled on behalf of the contributing community as material representations of its heritage and which are intended to be held in perpetuity for the information and enjoyment of present and future generations. Conservation is the chief means by which preservation is achieved and it has received increasing prominence as a scientific, technical and management activity in museums in the second half of the twentieth century. During the 1970s calls for improved standards of conservation in New Zealand's museums led central government to establish a ministerial advisory committee within the Department of Internal Affairs. This committee (the Interim Committee for the Conservation of Cultural Property) was to guide and facilitate collection conservation and the training of personnel through funding allocation and the provision of policy advice. It was replaced in 1987 by the Cultural Conservation Advisory Council, a similarly constituted body with a closely aligned mandate. These committees were formed during a period of interventionist government philosophy but since the mid 1980s New Zealand government has radically altered this stance and has withdrawn from service delivery in many areas. Government reforms have focused on the application of private market principles to the public sector, financial stringency and improved accountability. The Cultural Conservation Advisory Council was reviewed in 1991 and its activities discontinued. It is clear that shifting political philosophies had a strong influence on this outcome but there were several other contributing factors. The Council did not succeed in establishing an endorsed heritage policy for government and did not secure unified heritage sector support to advocate for its continuation. Since the Council's demise central government has not renewed its leadership role in promoting the conservation of New Zealand's cultural property. However, a number of discrete initiatives have arisen and important advances have been made in seeking to define government's role in heritage management and preservation generally and in the care of taonga Maori in particular. Australia has recently adopted a National Conservation and Preservation Policy for Moveable Cultural Heritage and is moving towards programme delivery in this area. This initiative may provide a useful model for New Zealand. As well as analysing central government's activities in cultural property conservation, this thesis points to the wider question of government's place in cultural activities generally and notes that traditional rationales and justifications must be reworked in light of new political philosophies in order to achieve a meaningful solution for communities and the heritage which they value.
Keywords: New Zealand. Interim Committee for the Conservation of Cultural Property; Cultural Conservation Advisory Council (N.Z.); Cultural property; Protection; New Zealand; Museum Studies; Government policy; Research Subject Categories::INTERDISCIPLINARY RESEARCH AREAS::Cultural heritage and cultural production